2018
DOI: 10.1093/jtm/tay042
|View full text |Cite|
|
Sign up to set email alerts
|

Aesthetic journeys: a review of cosmetic surgery tourism

Abstract: This narrative literature review focuses on the issues affecting travellers who obtain cosmetic surgical treatment overseas. There is a lack of focus in the travel medicine literature on the non-surgery-related morbidity of this special group of travellers. Original research exploring the motivation and pre-travel preparation, including the psychological counselling, of cosmetic surgical tourists is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…It is obvious that the degree to which persons are satisfied or dissatisfied with their own body has strong implication for their self-awareness, self-respect, and social behavior, as well as their attitudes towards acceptance of cosmetic procedures. Body image dissatisfaction impacts the quality of life, and it is believed to be a motivation for a number of body altering procedures as well as related activities (being on diets, getting informed about cosmetic procedures, saving money, medical tourism, and the like) [17,18]. This is further supported in our study by high scores for items such as, "It makes sense to Age treatment r = 0.015, p = 0.810 r = -0.075, p = 0.242 r = -0.073, p = 0.254 r = -0.058, p = 0.362 control r = 0.100, p = 0.116 r = -0.056, p = 0.378 r = 0.050, p = 0.436 r = 0.031, p = 0.621…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the degree to which persons are satisfied or dissatisfied with their own body has strong implication for their self-awareness, self-respect, and social behavior, as well as their attitudes towards acceptance of cosmetic procedures. Body image dissatisfaction impacts the quality of life, and it is believed to be a motivation for a number of body altering procedures as well as related activities (being on diets, getting informed about cosmetic procedures, saving money, medical tourism, and the like) [17,18]. This is further supported in our study by high scores for items such as, "It makes sense to Age treatment r = 0.015, p = 0.810 r = -0.075, p = 0.242 r = -0.073, p = 0.254 r = -0.058, p = 0.362 control r = 0.100, p = 0.116 r = -0.056, p = 0.378 r = 0.050, p = 0.436 r = 0.031, p = 0.621…”
Section: Discussionmentioning
confidence: 99%
“…15,34,35 A number of patients with obesity seek bariatric tourism to circumvent a long wait time. 20 Although medical tourism may seem attractive, foreign studies have reported that it is not without significant downfalls. 20 It is reported that bariatric surgery resolves both physical and mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although medical tourism may seem attractive, foreign studies have reported that it is not without significant downfalls. 20 It is reported that bariatric surgery resolves both physical and mental illnesses. 36 In fact, a patient with the most severe mental illness can benefit from bariatric surgery in a fashion similar to that a non-psychiatric patient would.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Berger et al in 2016 reviewed 417 English language websites for SC clinics. They found that the most common indication overall was skin care or anti-ageing (47.2%), while orthopaedic injuries, diabetes, multiple sclerosis and Parkinson's topped amongst medical illnesses (Berger et al, 2016;Terence et al, 2018).…”
Section: The Desire To Fulfil Today's Unmet Medical Needsmentioning
confidence: 99%